Analisis Keterlaksanaan Pembelajaran Biologi pada Kurikulum Merdeka di SMA Negeri Kota Padang - Nur Aisyah Putri; Lufri; Syamsurizal; Fitri Arsih; Suci Fajrina (Jurnal Penelitian Pendidikan IPA, 2024)
The Merdeka Curriculum is a curriculum policy that provides schools the freedom to develop a curriculum according to the needs and learning environment of the students. This curriculum, which has been in place for the past three years, must be evaluated on a micro level. This study aims to reveal the implementation of biology learning in the Merdeka Curriculum at State High Schools in Padang City. A survey method using a questionnaire instrument consisting of 70 statements regarding lesson planning, learning implementation, learning assessment, the Pancasila student profile, and learning obstacles was used to collect data. The research sample consisted of 34 biology teachers and 100 students at State High Schools in Padang City. The results showed that the aspect of lesson planning scored 78.78% in the good category, the aspect of learning implementation scored 80.82% in the good category, the element of learning assessment scored 79.26% in the good category, the aspect of the Pancasila student profile scored 78.04% in the good category, and learning obstacles scored 43.06% in the small category. Overall, the implementation of biology learning in the Merdeka Curriculum at State High Schools in Padang is in a good category with minor obstacles.